Real time path planning via alternating minimisation through image information. Issue 3 (17th August 2021) - Chen, Zheng; Zhang, Minjie; Zhu, Jiang; Zhu, Shiqiang
Abstract: Real time path planning from image information is of vital importance in the fields of robots as it has various applications in real time navigation, autonomous driving, robot arm manipulation and human robot cooperation and so on. To achieve this task, a two stage approach is proposed. At the first stage, a novel change point detection approach is proposed to process the image to extract the shape of the obstacles. At the second stage, several novel approximations are adopted to make the path planning problem tractable. Firstly, the irregular shapes of the obstacles in the environment are approximated as lines and circles, which simplify the distance constraint significantly. Secondly, the non‐convex path planning problem is iteratively decomposed as a sequence of subproblems and alternating minimisation method is proposed to efficiently solve the subproblem. To improve the quality of the solution, good initial points obtained by A* algorithm is provided. Both numerical experiments and real experiments are conducted to demonstrate the effectiveness of the proposed algorithm.